SOSIALISASI PERANAN EKOSISTEM MANGROVE PESISIR KUALA BUBON SEBAGAI UPAYA UNTUK MENUMBUHKAN KESADARAN SISWA/SISWI DI SEKOLAH SEKOLAH MENENGAH ATAS NEGERI 1 KECAMATAN SAMATIGA ACEH BARAT - Mohamad Gazali; Rina Syafitri (Universitas Teuku Umar, 2019)
The mangrove play an important role in protection of beach from wave, wind and hurricane. The pole of mangrove can protect home, building and agriculture from bad wind or water intrution. Mangrove forest are green belt have already destroyed and exploited illegally. Thus the penetrate of wave can destroyed many home, land inundated the agriculture. The activities were conducted in 5 November 2018 in Senior High School 1 Samatiga. The empowerment activity including the socialization of mangrove forest role to student of SMAN 1 Samatiga. The conducting method with using extension directly. There are working stage to solve the problem including the survey, exploration activity, the socialization and MONEV. The material of the socialization that we deliver such as the introduction of mangrove species Samatiga area and survey activities as well as the exploration of mangrove ecosystem. The aims of this activity is to introduce directly regarding mangrove ecosystem to student.